Effects of interface geometry on spin injection - Lee, B. C. (Journal of the Korean Physical Society, 2017)
Spin-injection efficiency may be affected by interface geometry and it was investigated theoretically by considering a nonmagnetic (NM) sphere embedded in a ferromagnetic (FM) host. When spin-polarized current is injected into the NM sphere from the FM host, it is found that spinsplitting of the electrochemical potential is enhanced at the interface while the spin polarization of the electrical current is reduced compared with the flat interface. In the Co/Cu and the Py/Cu systems, the values are different from those of the flat interface even when the sphere radius is 3 μ m. Attachment of another NM electrode to the NM sphere changes the spin-splitting of the electrochemical potential, which may be critical for the nonlocal spin signal in the lateral spin valve.